Navigating the medical journey: Insights into medical students' psychological wellbeing, coping, and personality. - Aisha Ali Hawsawi; Neil Nixon; Elena Nixon (PLoS ONE)
Background and aims In recent years, increased awareness of the psychological wellbeing of healthcare professionals and students has become a pressing public health issue affecting care delivery. Medical students undergo rigorous training programs that can affect their psychological wellbeing. Despite increased awareness of mental health issues among medical students, research often focuses on negative aspects, overlooking potential positive contributors to wellbeing. This study aims to explore both negative and positive factors influencing medical students' psychological wellbeing, considering coping strategies and personality traits to inform targeted support measures for diverse student needs. Methods A mixed-methods approach was employed to investigate medical students' psychological wellbeing, coping strategies, and personality traits. Quantitative data was gathered via self-report questionnaires and analysed using regression models. Additionally, qualitative insights were obtained from semi-structured interviews and analysed thematically to capture students' perceptions and experiences. Results The analysis revealed moderate to high levels of stress, anxiety, and depression among medical students, along with decreased life satisfaction. Regression analysis showed that problem-focused coping positively impacted medical students' psychological wellbeing, whereas emotion-focused and avoidance coping showed less favourable effects. Notably, problem-focused coping partially mediated the relationship between stress and depression. Furthermore, personality traits, particularly agreeableness and conscientiousness, played a pivotal role in shaping medical students' coping strategies and mental health outcomes. Based on thematic analysis, codes gave rise to three overarching themes and corresponding subthemes. Conclusions The study underscores the significance of addressing both positive and negative factors impacting medical students' wellbeing and highlights the need for tailored support considering individual personality traits that influence coping strategies and mental health. It also identifies challenges within medical education, emphasising the necessity for stress management programs, mental health support, and curricula promoting problem-solving skills. Prioritising medical students' wellbeing may not only foster good mental health among future professionals but may also enhance future healthcare quality.